10(x-2)-8=8x+6

Simple and best practice solution for 10(x-2)-8=8x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10(x-2)-8=8x+6 equation:


Simplifying
10(x + -2) + -8 = 8x + 6

Reorder the terms:
10(-2 + x) + -8 = 8x + 6
(-2 * 10 + x * 10) + -8 = 8x + 6
(-20 + 10x) + -8 = 8x + 6

Reorder the terms:
-20 + -8 + 10x = 8x + 6

Combine like terms: -20 + -8 = -28
-28 + 10x = 8x + 6

Reorder the terms:
-28 + 10x = 6 + 8x

Solving
-28 + 10x = 6 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-28 + 10x + -8x = 6 + 8x + -8x

Combine like terms: 10x + -8x = 2x
-28 + 2x = 6 + 8x + -8x

Combine like terms: 8x + -8x = 0
-28 + 2x = 6 + 0
-28 + 2x = 6

Add '28' to each side of the equation.
-28 + 28 + 2x = 6 + 28

Combine like terms: -28 + 28 = 0
0 + 2x = 6 + 28
2x = 6 + 28

Combine like terms: 6 + 28 = 34
2x = 34

Divide each side by '2'.
x = 17

Simplifying
x = 17

See similar equations:

| 10x+4+2x=103 | | 59-5x=14-10x | | Xsquared-x=17 | | 86=3x-12 | | [-2-3x]+x=9-x | | 5(x-3)+(x-4)=5x-6 | | 2xy+3xy=5xy | | 0.5-0.2=9.3 | | 72/u=8 | | 6x+10=-4-4x | | 4x+3=3+6x-8 | | 5x+8=66 | | 480/y=24 | | 5log^5(9-x)=6 | | 5(x-3)=13x-5 | | 100=10x+5y+0.5z | | 10m-13=57 | | g/8-5=8 | | 1/5x-2=15 | | 2+7x=8+x | | 8(x+3)=2x+66 | | x+1=10-8 | | 10z+4=54 | | 2+10x=-7x | | 6x+15=7x+13 | | w=67-21 | | 10+x=11+x | | 4=r^2/3 | | 2v-56=34 | | 12+4(w-5)=16-2w | | 7-7x-4=-71+5x-10 | | n+50=110 |

Equations solver categories